METABOLIC SYNDROME IN PATIENTS WITH LUPUS NEPHRITIS : Running title : Metabolic syndrome in lupus nephritis - Rabrenović, Dr sc. med. Violeta; Petrovic, Milica; Rabrenovic, Milorad; Rancic, Nemanja (Journal of Medical Biochemistry, 2024)
SUMMARYBackground: Metabolic syndrome (MetS) in the patients with SLE represents an additional burden and a poor prognostic factor for the onset or worsening of atherosclerosis and  cardiovascular complications. In many patients with lupus nephritis (LN) MetS is often already manifested initially. Our work aimed to determine the frequency and characteristics of MetS in patients with LN, as well as the relationship components of MetS and characteristics of disease activityMethods: The clinical study included 67 patients with LN, 54 (80.6%) female and 13 (19.4%) male, average age 42.86±14.46. Patients were divided into two groups: with MetS (35.8%) and without MetS (64.2%), active LN had (34 or 50.7%) and LN in remission (33 or 49.2%). We monitored clinical and biochemical parameters of interest.Results: Comparing patients with LN collectively, as well as those with MetS and without MetS, we observed that patients with MetS were older (p=0.001), BMI (p
Keywords: Keywords: lupus nephritis, metabolic syndrome, dyslipidemia, activity